2008
DOI: 10.1002/adfm.200701150
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Donor–Acceptor Regioregular Poly(3‐hexylthiophene)s Presenting Octylphenanthrenyl‐Imidazole Moieties Exhibit Enhanced Charge Transfer for Heterojunction Solar Cell Applications

Abstract: Intramolecular donor–acceptor structures prepared by covalently binding conjugated octylphenanthrenyl‐imidazole moieties onto the side chains of regioregular poly(3‐hexylthiophene)s exhibit lowered bandgaps and enhanced electron transfer compared to the parent polymer, e.g., conjugation of 90 mol% octylphenanthrenyl‐imidazole moieties onto poly(3‐hexylthiophene) chains reduces the optical bandgap from 1.91 to 1.80 eV, and the electron transfer probability is at least twice as high as that of pure poly(3‐hexylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 62 publications
1
53
0
Order By: Relevance
“…After photoexcitation, the generated excitons are stabilized and fur-ther separated because of the extended conjugation length, and the electrons are subsequently transferred from the donors to the acceptors very rapidly [6,7]. Furthermore, the charge separation and transfer process within the planar intramolecular donoracceptor structure is more effective than the one in the twisted intramolecular donor-acceptor structure, therefore, the charge transfer rate will be higher if the acceptor units are tethered on the polymeric main chains in a coplanar manner [5,6,8].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…After photoexcitation, the generated excitons are stabilized and fur-ther separated because of the extended conjugation length, and the electrons are subsequently transferred from the donors to the acceptors very rapidly [6,7]. Furthermore, the charge separation and transfer process within the planar intramolecular donoracceptor structure is more effective than the one in the twisted intramolecular donor-acceptor structure, therefore, the charge transfer rate will be higher if the acceptor units are tethered on the polymeric main chains in a coplanar manner [5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a new imidazole unit as the acceptor moiety has been synthesized by Neophytou et al [10] and this kind of copolymer exhibits fast exciton dissociation at the polymerfullerene heterointerfaces. Lee et al [11] also reported a kind of intramolecular donor-acceptor copolymer with electron-rich carbazole presenting in the backbone as the donor unit and electron-deficient 14H-benzo [4,5]isoquino[2,1-a]perimidin-14-one moiety as pendant side chains. In a recent report, we have presented a new kind of intramolecular donoracceptor copolymers containing side-chain-tethered perylenebis(dicarboximide) (PDI) moieties [12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations